Kinetics Extraction Modelling and Antiproliferative Activity of Clinacanthus nutans Water Extract - Farah Nadiah Mohd Fazil; Nur Syarafina Mohd Azzimi; Badrul Hisham Yahaya; Nurulain Atikah Kamalaldin; Saiful Irwan Zubairi (The Scientific World Journal, 2016)
Clinacanthus nutans is widely grown in tropical Asia and locally known “belalai gajah” or Sabah snake grass. It has been used as a natural product to treat skin rashes, snake bites, lesion caused by herpes, diabetes, fever, and cancer. Therefore, the objectives of this research are to determine the maximum yield and time of exhaustive flavonoids extraction using Peleg’s model and to evaluate potential of antiproliferative activity on human lung cancer cell (A549). The extraction process was carried out on fresh and dried leaves at 28 to 30°C with liquid-to-solid ratio of 10 mL/g for 72 hrs. The extracts were collected intermittently analysed using mathematical Peleg’s model and RP-HPLC. The highest amount of flavonoids was used to evaluate the inhibitory concentration (IC50) via 2D cell culture of A549. Based on the results obtained, the predicted maximum extract density was observed at 29.20 ± 14.54 hrs of extraction (texhaustive). However, the exhaustive time of extraction to acquire maximum flavonoids content exhibited approximately 10 hrs earlier. Therefore, 18 hrs of extraction time was chosen to acquire high content of flavonoids. The best antiproliferative effect (IC50) on A549 cell line was observed at 138.82 ± 0.60 µg/mL. In conclusion, the flavonoids content in Clinacanthus nutans water extract possesses potential antiproliferative properties against A549, suggesting an alternative approach for cancer treatment.